Entanglement enabled intensity interferometry in ultrarelativistic ultraperipheral nuclear collisions - James Daniel Brandenburg; Haowu Duan; Zhoudunming Tu; Raju Venugopalan; Zhangbu Xu (Physical Review Research)
An important tool in studying the subfemtoscale spacetime structure of matter in ultrarelativistic heavy-ion collisions is Hanbury Brown–Twiss (HBT) intensity interferometry of identical particles in the final state of the collisions. We propose that a variant of the entanglement enabled intensity interferometry (E^{2}I^{2}) framework introduced by Cotler and Wilczek can provide a powerful alternative to HBT interferometry in extracting fundamental nonperturbative features of quantum chromodynamics at high energies. We apply this framework to demonstrate that the spatial distributions of color singlet (pomeron) configurations in nuclei are sensitive to measurements of exclusive resonant decays of ρ mesons into π^{±} pairs in ultrarelativistic ultraperipheral nuclear collisions (UPCs) at the Relativistic Heavy Ion Collider and the Large Hadron Collider. A preliminary analysis suggests that the model-independent extraction of pomeron distributions will require careful treatment of the interplay of E^{2}I^{2} in the vector meson exclusive decay with the incoherent cross section for exclusive vector meson production. The E^{2}I^{2} framework developed here is quite general. It can also be employed as a tool to extract information on the spin structure of pomeron couplings as well as enhance the discovery potential for rare odderon configurations from exclusive vector meson decays into few-particle final states both in UPCs and at the Electron-Ion Collider.